Der Einfluss kognitiver und motivationaler Faktoren auf die Konstruktion hydrologischen Wissens – eine Analyse individueller Lernpfade - Reinfried, Sibylle (Journal of Geography Education, 2015)
What is it dependent on whether learners change their preconceptions? To study this question 12-year-old students' conceptual development of knowledge about water springs was explored using cognitive analysis of conceptual pathways. The aim of the study concerned the reconstruction of the students' knowledge development on water springs in mountain areas in order to better understand which factors are important for conceptual change. With a learning environment, whose efficacy was empirically reviewed beforehand, a group of ten students acquired knowledge of springs, in which their learning pathways were reconstructed from their written and oral statements. Data was obtained from student drawings and texts, knowledge tests, student interviews and videos of student work phases and evaluated using a structuring qualitative content analysis. In this paper, the knowledge construction and the individual learning pathways of two students are presented in form of case analyses. The two students display the range of possible individual learning pathways in an exemplary manner. The learners' previous knowledge proved to be decisive for the construction of knowledge but cognitive and motivational factors are just as influential. In particular previous knowledge, which was acquired through personal observations in social contexts, is distinguished by great stability so that inconsistencies between previous knowledge and instructional knowledge are not perceived in the learning process and despite great interest, very little progress in learning is achieved.
Keywords: preconceptions, conceptual change, hydrological knowledge, cognitive analysis of conceptual pathways, mental model development